An Analysis of Figurative Language of Beauty Advertisement in English Magazines - Dinda Novinda Haryani; Jismulatif; Dahnilsyah (Bedelau: Journal of Education and Learning, 2024)
This study analyzes the use of figurative language in beauty advertisements found in English magazines. The primary objective is to identify and interpret the types of figurative expressions employed in these advertisements and explore their effect on consumer perception and behavior. The research focuses on examining various figurative devices such as metaphors, similes, personification, hyperbole, and symbolism, and how these devices are used to enhance the appeal and persuasive power of beauty products. By analyzing a selection of advertisements from popular English magazines, the study demonstrates how figurative language is strategically utilized to create emotional appeal, shape brand identity, and influence purchasing decisions. The findings indicate that figurative language plays a crucial role in enhancing the emotional connection between consumers and beauty products, thereby contributing significantly to the effectiveness of advertising campaigns. This analysis highlights the importance of linguistic creativity in advertising, particularly in the beauty industry, where image and perception are central to marketing strategies.